Hepatitis C virus treatment and survival in patients with hepatitis C and human immunodeficiency virus co‐infection and baseline anaemia. Issue 7 (25th April 2013) - Erqou, S.; Mohanty, A.; McGinnis, K. A.; Vanasse, G.; Freiberg, M. S.; Sherman, K. E.; Butt, A. A.
Summary The impact of pretreatment anaemia on survival in individuals with hepatitis C virus (HCV) and human immunodeficiency virus (HIV) co‐infection is not known. Moreover, HCV treatment is offered less frequently to individuals with anaemia, due to haematological side effects of the treatment regimen. This study aimed to determine the effect of HCV treatment on survival among HCV/HIV co‐infected individuals with pretreatment anaemia using the Electronically Retrieved Cohort of HCV‐Infected Veterans (ERCHIVES). Individuals with HCV/HIV co‐infection were included in current analyses. Participants were considered treated if they were prescribed ≥4 weeks of HCV treatment. All‐cause mortality data were obtained using record linkage. Survival analyses were performed using Cox proportional hazard models. Among 5000 HCV/HIV co‐infected individuals, 1671 (33.4%) had pretreatment anaemia. In a follow‐up period of up to 7 years (19 500 person‐years), individuals with anaemia had significantly higher mortality rate compared with those without anaemia [144.2 (95% CI: 134.5–154.7) vs 47.5 (44.0–51.2) per 1000 person‐years, respectively]. Among individuals with anaemia, HCV treatment was associated with significantly lower mortality rate [66.6 (44.3–100.2) vs 149.6 (139.2–160.5) per 1000 person‐years, for treated vs untreated, respectively]. Treatment remained associated with substantial survival benefit after taking into account the effect of multiple comorbidities (hazards ratio: 0.34, 95% CI: 0.21–0.62). These data suggest that HCV/HIV co‐infected individuals with pretreatment anaemia have significantly higher mortality compared with those without anaemia. HCV treatment is associated with substantial survival benefit in this group. Additional studies are needed to determine strategies to improve HCV treatment rates among this group.